1999
DOI: 10.1093/ije/28.4.614
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and male lung cancer risk with special regard to type of tobacco

Abstract: The main results of the study (a higher LC risk among black tobacco users than in exclusive blond tobacco users, and a lower LC risk among long-term filter-tipped cigarette smokers than all other smokers) have been consistent with previous case-control studies and with ecologic studies which took into account past exposure levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This discrepancy may be due to the fact that our "average smoker" had higher cumulative exposure and quit smoking more rarely and more recently compared with other study populations [5,6,[25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This discrepancy may be due to the fact that our "average smoker" had higher cumulative exposure and quit smoking more rarely and more recently compared with other study populations [5,6,[25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies [5,16,25,28,29,[33][34][35] reported an effect of age started, although some found no effect [36][37][38][39]. Most of these studies failed to account for confounding by duration, which is naturally correlated with age started or by years since quitting.…”
Section: Discussionmentioning
confidence: 99%
“…Filter vs nonfilter smoking and lung cancer histology T Marugame et al overall, although filter cigarette smokers were at lower risk compared to nonfilter smokers regardless of histology, a greater reduction in adjusted OR was observed for SCC than for AC. Lower risk of all lung cancers has been observed among filter cigarette smokers compared to nonfilter cigarette smokers in some case -control studies of men (Wynder and Stellman, 1979;Lubin et al, 1984;Benhamou et al, 1989;Benhamou et al, 1994;Armadans et al, 1999) and women (Wynder and Stellman, 1979;Lubin et al, 1984;Agudo et al, 2000). However, the reduction in risk of all lung cancers among filter cigarette smokers compared to nonfilter cigarette smokers has been obscured.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies (Ives, 1984;Alderson et al, 1985;Benhamou et al, 1987Benhamou et al, , 1994Garfinkel & Stellman, 1988;Agudo et al, 1994;de Stefani et al, 1996b;Stellman et al, 1997;Armadans-Gil et al, 1999) used a comparison group of "filter only" based on lifetime smoking history. From the 14 gender-specific estimates, the relative risk was 0.64 (0.53 to 0.78).…”
Section: Filter Cigarettesmentioning
confidence: 99%